2006
DOI: 10.2143/ac.61.6.2017959
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors in first degree relatives of patients with premature coronary artery disease

Abstract: The prevalence of coronary risk factors among first-degree relatives of patients with premature CAD is high, especially in men. Risk factor identification and modification should be considered in individuals with a positive family history of premature CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 0 publications
1
9
0
1
Order By: Relevance
“…19 Saghafi et al found prevalence of hypertension in firstdegree relatives men as 53.2% and women 24.7%. 12 Kang et al study in first-degree relative showed hypertension prevalence as 25% and mean systolic blood pressure as 132 ± 19 mmHg which is comparable to present study mean of 136 ± 7 mmHg. 18 Around 14% males belonged to the hypertensive group, whereas only 5% females had hypertension in the study.…”
Section: Ethical Issuessupporting
confidence: 87%
See 2 more Smart Citations
“…19 Saghafi et al found prevalence of hypertension in firstdegree relatives men as 53.2% and women 24.7%. 12 Kang et al study in first-degree relative showed hypertension prevalence as 25% and mean systolic blood pressure as 132 ± 19 mmHg which is comparable to present study mean of 136 ± 7 mmHg. 18 Around 14% males belonged to the hypertensive group, whereas only 5% females had hypertension in the study.…”
Section: Ethical Issuessupporting
confidence: 87%
“…19 In study of Saghafi et al over weight prevalence in first-degree relatives men was 56.3% and women 39.7% which is also comparable to this study findings. 12 Among 33% of study subjects had self-reported history of hypertension, 71% were pre hypertensive and 29.2% were hypertensive grade1. About…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Individuals who smoked regularly during the previous 12 months were classified as smokers. Other risk factors as lack of exercise and family history of premature CAD (first degree male relatives <55 years or females <65 years) were documented [29]. …”
Section: Methodsmentioning
confidence: 99%
“…Em contrapartida, alguns autores referem alterações glicêmicas em menos de 10% dos familiares de primeiro grau. 125 A elevada presença de sobrepeso/obesidade e SM neste grupo possivelmente justifica este achado.…”
Section: Avaliação Da Associação Entre Função Tireoidiana E Parâmetrounclassified